Augmenting organizational development at a faculty through team building activities - Mohammed Musa, Ahmad Yahya; Ismail, Ismi Arif; Suandi, Turiman; Krauss, Steven Eric (2011)
In order to continuously develop itself as an organization, a university management relies on a strong pool of human resources which includes academics, administrative officers and support staff. Organizational development is a continuous effort at helping people to enjoy working together as a team towards reaching their individual and organizational goals (French & Bell, 1995; Bolman & Deal, 1997). Team building activity is one of the mechanisms used by organization to develop strong human resources (Finger & Brand, 1999; Philips & Elledge, 1989; Prichard & Ashleigh, 2007; Senge, 1990; Senge et. al, 2000). Like other learning organizations, universities are also moving towards using team building activities in their organizational development exercises. However, it is interesting to investigate to what extent do team building activities which are normally carried out within and outside campus affect staff morale and spirit of working as a team. This study aims to evaluate the impact of team building activities on faculty organizational development. Additionally, it examines how the entire team building program is planned, implemented and evaluated. The findings of the study are anticipated to contribute to the knowledge on how and what types of team building activities can assist universities in developing their human resources.